Negotiating in Silence: Experiences with Parental Leave in Academia - Weststar, Johanna (Relations industrielles / Industrial Relations, 2012)
This paper presents a case study of pregnancy/parental leave arrangements among faculty members at a mid-sized Canadian University from 2000-2010. The data show that leave arrangements were very inconsistent across faculties, across and within departments, and even for individual faculty members who had taken more than one leave. The majority of problematic cases were instances where a faculty member began or ended a leave in the middle of an academic term. Without specific language in their collective agreement, these faculty members often negotiated circumstances that carried individual penalties for duties that were unassigned in light of the leave. This research has implications for unions who must be particularly vigilant and active in professional environments where individual negotiation takes place and union consciousness is lower. It also emphasizes the burden placed on parents when the bearing and rearing of children is framed as an individual right rather than an issue of social reproduction. The paper uses data from a sample of collective agreements across Canadian universities to make recommendations to clarify the procedures for pregnancy and parental leave.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Colleges & universities; Labor Unions; Labor relations; Maternity & paternity leaves; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; University faculty

Research Handbook of Employment Relations in Sport - Weststar, Johanna (Relations industrielles / Industrial Relations, 2019)
The article reviews the book, "Research Handbook of Employment Relations in Sport," edited by Michael Barry, James Skinner and Terry Engelberg.

Comment jouer la régulation dans l’industrie du jeu vidéo? - Legault, Marie-Josée; Weststar, Johanna (Relations industrielles / Industrial Relations, 2014)
Cet article étudie les choix des concepteurs de jeux vidéo en matière de représentation de leurs intérêts à la lumière de la théorie de la mobilisation de Kelly (1998), cela dans le but de mesurer leur disposition à l’action collective. Ces travailleurs illustrent bien le cas des travailleurs du savoir dans des productions organisées par projets. Si le modèle de Kelly permet en principe d’asseoir des projections concernant la syndicalisation d’un secteur, tel n’est pas le cas ici. Notre étude nous amène plutôt à mesurer l’ampleur de la transformation du marché de l’emploi depuis l’élaboration du modèle et la distance qui sépare les besoins des travailleurs du savoir, d’une part, et les options que leur propose l’action syndicale traditionnelle telle que présentée par le modèle de Kelly, d’autre part.Ce groupe de travailleurs remplit deux conditions propices à l’action collective : il a identifié des problèmes communs dans les conditions de travail de l’industrie et il en attribue généralement la responsabilité à l’employeur.Cependant, trois conditions essentielles l’empêchent de s’unir en une coalition. D’abord, il est partagé entre une définition de son intérêt en termes collectifs et individuels; ensuite , il est aussi partagé quant à la conviction que la situation insatisfaisante est illégitime. Enfin, et surtout, lorsque les travailleurs analysent les coûts et les bénéfices de l’action collective, le projet de syndicalisation via le régime général d’accréditation fondé sur l’entreprise-employeur leur pose plusieurs problèmes concrets. Les concepteurs de jeux pratiquent une forme d’action collective qui contourne les contraintes que pose notre régime juridique actuel de rapports collectifs de travail. Or, la théorie de la mobilisation de Kelly assimile action collective et action syndicale traditionnelle, ce qui mérite d’être reconsidéré.
Keywords: Diseñadores de juegos de video; acción colectiva; action collective; collective action; concepteurs de jeux vidéo; knowledge workers; organisation par projets; organización por proyectos; project-based organisations; sindicalización; syndicalisation; trabajadores del saber; travailleurs du savoir; unionisation; video game developers